Dynamic algorithm for linear quadratic Gaussian predictive control - Ordys, Andrzej W.; Hangstrup, Mads E.; Grimble, Michael J. (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, the optimal control law is derived for a multi-variable state-space Linear Quadratic Gaussian Predictive Controller (LQGPC). A dynamic performance index is utilized resulting in an optimal steady-state controller. Knowledge of future reference values is incorporated into the controller design and the solution is derived using the method of Lagrange multipliers. It is shown how the well-known GPC controller can be obtained as a special case of the LQGPC controller design.
Keywords: state-space design; multi-variable control; linear quadratic Gaussian predictive control; generalized predictive control